MODEL INDUSTRI BISNIS MEDIA MASSA PADA ERA PERKEMBANGAN ARTIFICIAL INTELLIGENCE (AI) DI INDONESIA: - - Saidah, Iis (Linimasa : Jurnal Ilmu Komunikasi, 2021)
Abstract This study aims to contsruct a mass media bussiness industry model in the era of artificial intelligence (AI) development in Indonesia. The development of artificial inteligence technology in Indodesia, espesially in mass media industry, makes it possible to apply this technology. The object of the study in mass media bussiness industry model in AI development era is bussiness communication and the subjects are informants from mass media who apply digital in running their bussines. This study was designed as qualitative study with contsruction paradigm and case study analysis. The results of the study are 1). The bussiness industry concept of mass media “Ayo Bandung” in the era of AI development have a role as bussiness booster “Ayo Media” in an integrated solution communication bussiness with one window service concept. Ayo Bandung develops an online news and through more social media actively with news content more focus on regional news emphasizing in basic bussiness aspect, target market and creativity looking for ideas for creating regeneration 2). Mass media bussiness industry model whichis Ayo Bandung have 10 keys the era of artificial intelligence development, including Customer Segment​, Value Proposition, Channels, Customer Relationship, Revenue Streams, Key Resource, Key Activities, Key Partnership, Cost Structure dan Technology Applied